2009
DOI: 10.1016/j.neuroimage.2008.12.071
|View full text |Cite
|
Sign up to set email alerts
|

Multiexponential T2 and magnetization transfer MRI of demyelination and remyelination in murine spinal cord

Abstract: Identification of remyelination is important in the evaluation of potential treatments of demyelinating diseases such as multiple sclerosis. Local injection of lysolecithin into the brain or spinal cord provides a murine model of demyelination with spontaneous remyelination. The aim of this study was to determine if quantitative, multicomponent T2 (qT2) analysis and magnetization transfer ratio (MTR), both indicative of myelin content, could detect changes in myelination, particularly remyelination, of the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 58 publications
2
84
0
2
Order By: Relevance
“…For specifically identifying axon injury and loss, reduced NAA content measured by magnetic resonance spectroscopy (MRS) has been used (De Stefano et al, 1999;Aboul-Enein et al, 2010;Wood et al, 2012). However, inflammation can interfere with measuring myelin and axons because inflammation-induced tissue swelling falsely reduces the measured myelin water and NAA content (oedema water contains no NAA and dilutes myelin water fraction), MTR (oedema water exhibits no transfer effect while contributing to the total signal), and PET marker intensity (diluting marker density) (Schmierer et al, 2004;Stanisz et al, 2004;McCreary et al, 2009;Vavasour et al, 2011). Despite that DTI-derived axial diffusivity and radial diffusivity can concurrently quantify coexisting axonal injury and demyelination in some settings (Song et al, 2002(Song et al, , 2003(Song et al, , 2005, DTI becomes inaccurate in the presence of inflammation (Sun et al, 2006b;Lodygensky et al, 2010;Xie et al, 2010), tissue loss (Kim et al, 2007), crossing fibres (Wheeler-Kingshott and Cercignani, 2009), and CSF contamination (Karampinos et al, 2008;Cheng et al, 2011) and cannot measure the inflammatory components.…”
Section: Discussionmentioning
confidence: 99%
“…For specifically identifying axon injury and loss, reduced NAA content measured by magnetic resonance spectroscopy (MRS) has been used (De Stefano et al, 1999;Aboul-Enein et al, 2010;Wood et al, 2012). However, inflammation can interfere with measuring myelin and axons because inflammation-induced tissue swelling falsely reduces the measured myelin water and NAA content (oedema water contains no NAA and dilutes myelin water fraction), MTR (oedema water exhibits no transfer effect while contributing to the total signal), and PET marker intensity (diluting marker density) (Schmierer et al, 2004;Stanisz et al, 2004;McCreary et al, 2009;Vavasour et al, 2011). Despite that DTI-derived axial diffusivity and radial diffusivity can concurrently quantify coexisting axonal injury and demyelination in some settings (Song et al, 2002(Song et al, , 2003(Song et al, , 2005, DTI becomes inaccurate in the presence of inflammation (Sun et al, 2006b;Lodygensky et al, 2010;Xie et al, 2010), tissue loss (Kim et al, 2007), crossing fibres (Wheeler-Kingshott and Cercignani, 2009), and CSF contamination (Karampinos et al, 2008;Cheng et al, 2011) and cannot measure the inflammatory components.…”
Section: Discussionmentioning
confidence: 99%
“…Removing the Rayleigh noise floor eliminated the CSF peak in TPC data analysis; therefore TPC analysis removes a potential artefact commonly assigned to CSF from decay data that does not contain CSF. Consequently, if the decay data are collected such that the noise floor is not reached, this Rayleigh noise floor artefact should be absent, which could explain the absence of the CSF peak in tumor and normal rat brain at 7 T [10] and a 9.4 T study of murine spinal cord [16].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple echo fitting, using non-negative least squares (NNLS) [5], can be performed to determine the relative proportions of the micro-structural dependent T 2 times [6,7,8,9,10]. In some cases, such as healthy [3,4,11,12] and pathological [13,14,15,10,16] central nervous system tissue, different water environments with separate T 2 times are present within a given voxel, resulting in a decay curve from the voxel being the summation of exponential decays from each constituent T 2 time. Four regions are of particular interest: 1) one with a short T 2 time attributed to water trapped between myelin bilayers, called myelin water; 2) one with an intermediate T 2 time attributed to intra-and extracellular water; 3) one with a prolonged T 2 time longer than intra-and extracellular water, which has been noted in pathology [13,14] and in the corticospinal tract of healthy volunteers [13,17]; and 4) one with the longest T 2 time in the distribution, or near that of pure water, that is attributed to cerebrospinal fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In the experimental allergic encephalomyelitis model of multiple sclerosis, contrast changes have been observed in conventional anatomic images (Schellenberg et al, 2007), axial diffusivity has been correlated with axonal damage (Budde et al, 2008;Budde et al, 2007;Budde et al, 2009), and decreased quantitative T2 and magnetic transfer values have been shown (McCreary et al, 2009). Numerous studies have also assessed white matter integrity in mouse models of spinal cord injury, using diffusion tensor imaging Kim et al, 2010;Loy et al, 2007;Tu et al, 2010), T1-and T2-weighted imaging (Gonzalez-Lara et al, 2009;Levene et al, 2008;Nishi et al, 2007), and MRM (Bilgen, 2007).…”
Section: Introductionmentioning
confidence: 99%